Programas de intervenção com agressores como condição de suspensão condicional do processo nos crimes de violência doméstica contra a mulher - Dhein, Cássia Saraiva (Universidade do Vale do Rio dos Sinos, 2019)
The phenomenon of domestic violence against women was, for many in society, naturalized by the social construction of male supremacy and female subordination, even though unconsciously. This naturalization entails, by the aggressors, the incomprehension of the imposition of a custodial sentence on these crimes, since a man, not infrequently, believes that he has the right to assault his partner and the victim, for her turn, does not see this behavior as aggressive. The punishment derived from the model of retributive justice, for its turn, has already proved to be notoriously flawed. Therefore, means of diversion are sought from the traditional criminal procedure, through restorative and consensual justice, mainly due to the applicability of the conditional suspension of the process to these crimes and the establishment of intervention programs for batterers. This paper aims to analyze the intervention programs used in the United States, Colombia and Portugal, as a basis for applying similar projects in the Brazilian legal system. In particular, it is intended to investigate the feasibility of the conditional suspension of the process to crimes of domestic violence in Brazilian law, despite the express prohibition of the institute for the judgments of the Direct Action of Unconstitutionality n. 4424 and the Declaratory Action of Constitutionality n. 19 by the Brazilian Supreme Federal Court, based on the condition of compulsory attendance of aggressors of domestic violence on intervention programs with batterers, using, therefore, the Portuguese experience of provisional suspension of the process.
Keywords: Violência doméstica contra mulheres; Meios de diversão penal; Suspensão condicional do processo; Programas de intervenção para agressores; Domestic violence against women; Means of criminal diversion; Conditional suspension of the process; Intervention programs for batterers